Long-term survival of a cat with primary leiomyosarcoma of the urinary bladder - Buzatto, Anneliese Baetz; Elias, Fabiana; Franzoni, Mayara Simão [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (MDPI, 2019)
Primary bladder leiomyosarcoma was diagnosed in a four-year-old, mixed-breed, spayed female cat that presented with lethargy, stranguria, polyuria, hematuria, urinary incontinence and abdominal sensitivity. On abdominal ultrasound, the urinary bladder was observed to have a preserved anatomical position and a hyperechoic mass. The mass measured approximately 1.5 cm, was irregular, and arose from the mucosa of the bladder wall. Due to the evidence of a primary tumor in the urinary bladder, we conducted a partial cystectomy with a 1.0 cm surgical margin and performed histopathology and immunohistochemistry. The histopathology revealed a poorly differentiated malignant neoplasm, characterized by the proliferation of spindle cells with moderate nuclear pleomorphism, suggestive of leiomyosarcoma. Immunohistochemistry confirmed the histopathological diagnosis, showing positive staining for vimentin, desmin and alpha-smooth muscle actin and negative staining for S100, pan-cytokeratin and MyoD1. We also assessed the proliferative index by Ki67 staining and found that 57% of the neoplastic cells were positive for Ki67. We conducted clinical follow-ups every three months in the first year and every six months thereafter. The patient showed no signs of recurrence after 48 months. The surgery was sufficient to treat the leiomyosarcoma, and adjuvant chemotherapy was not necessary in this case.
Keywords: Cat; Leiomyosarcoma; Urinary bladder